Subjects and rights-based approach: Social Work students' perceptions - Martínez Flores, Bertha Verónica; Ortiz Aguilar , Leticia (Interacción y Perspectiva, 2024)
The present article aims to analyze Social Work students' perceptions regarding subjects of rights within the community-level intervention. The study focuses on the Methodology and Practice of Social Work in Community I and II, as part of a bachelor's program in social work at a university in northern Mexico. Integrating a rights-based approach into the profession prompts reflection on conceptualizing the intervention subject as a rights holder, emphasizing the significance of this transformative aspect in student education. Utilizing various qualitative data collection techniques, it becomes evident that the student clearly understands the importance of citizenship, with the concept of the subject of rights consistently linked to it. This alignment encourages the profession as future social workers to embrace a rights-oriented perspective in their practice. However, there remains a need to delve into discussions surrounding the individual as a rights holder, gaining clarity on the State's role in assuming obligations and emphasizing the significance of public policies in achieving the well-being of communities.